Underpass Development on the Train Cross, South Tambun Bekasi - Rida Zakiyah; Prasadja Ricardianto; Abdullah Ade Suryobuwono; Masjraul Hidayat (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
This study aims to improve safety and security for vehicle users passing through the tunnel, identify the construction of underpasses at railroad crossings, minimize queue lengths and delays while crossing on Jalan Sultan Hasanudin, Pasar Tambun, Bekasi and improve road smoothness, and provide recommendations for the need for pedestrian facilities on the Jalan Sultan Hasanudin section. There is a potential safety risk for pedestrians, because there are no pedestrian crossing facilities. Then analyze the benefits of underpass construction on level crossings for road users.  The method used is descriptive quantitative analysis, namely in the form of calculating traffic performance, technical requirements of the railway line, the benefits of the underpass for train operations and the need for pedestrian crossing facilities. The results of the analysis identify the need for underpass maintenance costs for safety and security for passing vehicle users. It is necessary to add a zebra cross and pelican on Jalan Sultan Hasanudin on pedestrian facilities to cross, close the u-turn of the Ataqwa mosque which is moved to the u-turn access of the police station, south Tambun, then the construction of the tunnel is very useful for rail operations and road users.